2018
DOI: 10.1117/1.jbo.23.12.126002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of glycosaminoglycan loss in articular cartilage by fluorescence lifetime imaging

Abstract: Glycosaminoglycan (GAG) loss is an early marker of osteoarthritis, which is a clinical late stage disease that affects millions of people worldwide. The goal of our study was to evaluate the ability of a fiber-based fluorescence lifetime imaging (FLIm) technique to detect GAG loss in articular cartilage. Native bovine cartilage explants (n ¼ 20) were exposed to 0 (control), 0.5 (low), or 1 U∕mL (high) concentrations of chondroitinase ABC (cABC) to create samples with different levels of GAG loss. FLIm assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Inducing proteolytic damage in cartilage tissue resulted in significant decrease in AFL in murine, porcine and human joints. These measurements confirmed previous observations 15,24 , demonstrating that AFL is sensitive to biochemical alterations in the cartilage ECM caused by disruption of collagen crosslinks or aggrecan depletion from tissue. In particular, we observed a decrease in the AFL of fresh human metatarsophalangeal articular cartilage treated with RA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Inducing proteolytic damage in cartilage tissue resulted in significant decrease in AFL in murine, porcine and human joints. These measurements confirmed previous observations 15,24 , demonstrating that AFL is sensitive to biochemical alterations in the cartilage ECM caused by disruption of collagen crosslinks or aggrecan depletion from tissue. In particular, we observed a decrease in the AFL of fresh human metatarsophalangeal articular cartilage treated with RA.…”
Section: Discussionsupporting
confidence: 90%
“…We have previously reported that AFL can report proteolytic damage of ex vivo cartilage tissue that includes aggrecan degradation in porcine cartilage pieces 15 . Similar work by others demonstrated that AFL can report glycosaminoglycan (GAG) depletion in bovine articular cartilage 24 . In this study, we investigated the potential of AFL to report areas of proteolytically damaged human cartilage.…”
Section: Discussionsupporting
confidence: 58%
“…In contrast, native cartilage has a large depth‐dependent variation in biochemical composition. When we subjected native tissue to enzymatic treatments to deplete matrix content, we found lower than expected differences in fluorescence signal in cartilage imaged perpendicular to the tissue surface as compared with cartilage imaged in cross section (Zhou et al, ).…”
Section: Discussionmentioning
confidence: 60%
“…To illustrate the potential to report intrinsic contrast in a clinically relevant application, porcine articular cartilage samples were mapped before and after localized treatment with bacterial collagenase (see Figures , S10‐S14 and Video S4) to promote cleavage of collagen type II fibrils and depletion of proteoglycan content, which are known to affect the fluorescence lifetime of cartilage . Before treatment (see Figure A,C,E), we measured an average lifetime of 6.89 ± 0.45 ns over the entire sample, for a total acquisition time of 30.8 seconds (n = 1528 measurements, resulting in an average TCSPC rate of 49.6 Hz).…”
Section: Resultsmentioning
confidence: 99%